2015
DOI: 10.1007/s00464-015-4319-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase II clinical experience and long-term follow-up using the next-generation single-incision platform FMX314

Abstract: This study demonstrates that single-incision cholecystectomy with the platform is feasible, safe, and reproducible in a larger patient population. Long-term follow-up showed no hernias or other adverse events. Further studies will be needed to evaluate longer-term hernia rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…In our previous studies, we demonstrated the feasibility of surgical procedures using the SymphonX platform [3,4,11]. This study now addresses, how laparoscopic novices, medical students without any laparoscopic experience, are able to deal with the new device.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In our previous studies, we demonstrated the feasibility of surgical procedures using the SymphonX platform [3,4,11]. This study now addresses, how laparoscopic novices, medical students without any laparoscopic experience, are able to deal with the new device.…”
Section: Discussionmentioning
confidence: 93%
“…Since its introduction to clinical practice laparoscopic surgery underwent an enormous development [1,2]. The pathway of minimally invasive surgery until the most recent milestones such as single-port and robotic surgery has been reported before [3][4][5][6][7][8][9][10][11][12]. In this context, we recently described our first preclinical experience with a newly developed single-port device, fitting through a standard 15-mm trocar [3,4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our group focused on developing an endoscopic suturing-technique using a standard flexible endoscope and the newly designed, flexible, articulating instrument (EndoSuture, Fortimedix-Surgical BV, Geleen, Netherlands) allowing for complex end-effector movements [12,13]. Initially we set up prerequisites.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we investigate a novel minimally invasive surgical platform for its utility in the transoral approach to the oropharynx, hypopharynx, and larynx. The Fortimedix Surgical B.V. symphonX™ single-port surgical platform is FDA approved for minimally invasive abdominal laparoscopic surgery and has been described for use in laparoscopic cholecystectomy [ 14 , 15 ]. This platform has been adapted from a single-port laparoscopic device and modified to allow introduction via a surgical laryngoscope for use in the transoral approach to the upper aerodigestive tract.…”
mentioning
confidence: 99%